Values and countervalues of the Culture of peace in Spanish football: Virtual Environment Analysis - Ossorio Núñez, Margarita; Morgado Poveda, Sergio (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2022)
Footbal social networks are supposed to be a new space where people highly interact. This fact could lead to the emergence of hate speech. We are going to analyze the hate speeches amongst football fans. To reach this aim, we use cualitative method by the virtual ethnography technic, making both a content and discursive analysis from the most important social forum in Spain. In spite of the presence of rules in the forums, we have found out that these virtual spaces are frecuently used by users to manifest hate speeches against other members of the community, causing unsportsmanlike conduct.